Design, calibration, and validation of an inline green coffee moisture estimation system using time-domain reflectometry - Laudia Anokye-Bempah; Kittisak Phetpan; David Slaughter; Irwin R. Donis-Gonzlez (My University, 2022)
Wet basis moisture content (MCwb) is an important quality parameter of green coffee as it affects the coffee's physical, chemical, and sensory characteristics. Accurate estimation of green coffee MCwb after dry hulling, long-term storage, and transportation is imperative to prevent quantitative and qualitative losses. Thus, this study aimed to design, develop, calibrate and validate a prototype inline system capable of accurately measuring the MCwb of green coffee beans, using a commercially available time-domain reflectometry (TDR) probe. The TDR probe was calibrated and validated with green coffee within a MCwb range of 9–21%. A calibration linear regression model correlating the TDR probe output (dielectric constant) to reference MCwb measurements obtained by a halogen moisture analyzer, yielded a high coefficient of correlation (R2 = 0.99). Model validation yielded a high R2, and a low Root Mean Squared Error equal to 0.93, and 0.9% MCwb, subsequently. Results indicate that the TDR inline green coffee moisture estimation system has the potential to be applied in real-time, industrial-scale operations.
Keywords: Reflectometry; Green coffee; Soil Moisture and Remote Sensing